-4n2+8=4

Subtract 8 from both sides of the equation.

-4n2=4-8

Subtract 8 from 4.

-4n2=-4

-4n2=-4

Divide each term in -4n2=-4 by -4.

-4n2-4=-4-4

Cancel the common factor of -4.

Cancel the common factor.

-4n2-4=-4-4

Divide n2 by 1.

n2=-4-4

n2=-4-4

Divide -4 by -4.

n2=1

n2=1

Take the square root of both sides of the equation to eliminate the exponent on the left side.

n=±1

Any root of 1 is 1.

n=±1

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

n=1

Next, use the negative value of the ± to find the second solution.

n=-1

The complete solution is the result of both the positive and negative portions of the solution.

n=1,-1

n=1,-1

n=1,-1

Solve for n -4n^2+8=4